IMPROVED INFORMATION COMMUNICATION METHODOLOGY WITH SECURED BACKUP CONFINED NODES FORWSN DESIGN - RAKESH K K; T ELANGOVAN; S VIJITHA; BOOPATHI KUMAR E (The Bioscan, 2025)
Wireless Sensor Networks (WSNs) are increasingly utilized in critical monitoring applications, yet their constrained resources and deployment in hostile environments make them vulnerable to security threats and data loss. This paper proposes an Enhanced Secured Data Transmission Methodology (ESDTM) integrated with Backup Protected Nodes (BPNs) to ensure reliable and secure data delivery across the network. The proposed approach incorporates lightweight encryption for secure communication and a dynamic backup node allocation mechanism to mitigate the impact of node failures or malicious attacks. Simulation results demonstrate that ESDTM with BPNs significantly improves packet delivery rate, reduces data loss, and enhances energy efficiency compared to conventional WSN protocols. This methodology is particularly suitable for mission-critical WSN applications, offering improved fault tolerance and security assurance.